IDENTIFIKASI KEMAMPUAN BERPIKIR KRITIS DALAM MEMECAHKAN MASALAH MATEMATIKA - Ardi Dwi Susandi (SIGMA, 2020)
This Mathematics critical thinking skill is one of the components a student must possess. This skill will assist them to be able to make the right decision. In fact, however, not many of them having a high of critical thinking skill. It causes them to be lack of skills in completing the mathematics cases. This research aims to: (1) describe the critical thinking skills of junior high school students in solving mathematical problems and (2) identify the students' critical thinking components in the focus, reason, inference, situation, clarity, dan overview. This was descriptive research with a qualitative approach. This research involved 32 subjects comprising 15 male students and 17 female students. The method used in this research is test, interview, and triangulation. The test used in this research consisted of 6 problems representing 6 sub-skills of critical thinking skills. The results of data collection were analyzed through data reduction, data display, and conclusion drawing. The findings showed that: (1) the critical thinking skills of junior high school students were in a low category; (2) overview became the lowest critical thinking sub-skills mastered by the students compared to other critical thinking sub-skills